Tsc Gene Locus Disruption and Differences in Renal Epithelial Extracellular Vesicles - Kumar, Prashant; Zadjali, Fahad; Yao, Ying; Siroky, Brian; Astrinidis, Aristotelis; Gross, Kenneth W.; Bissler, John J. (Frontiers in Physiology, 2021)
In tuberous sclerosis complex (TSC), Tsc2 mutations are associated with more severe disease manifestations than Tsc1 mutations and the role of extracellular vesicle (EVs) in this context is not yet studied. We report a comparative analysis of EVs derived from isogenic renal cells except for Tsc1 or Tsc2 gene status and hypothesized that in-spite of having similar physical characteristics, EVs modulates the signaling pathways differently thus leads to TSC heterogenicity. We used mouse inner medullary collecting duct (mIMCD) cells with the Tsc1 (T1G cells) or Tsc2 (T2J cells) gene disrupted by CRISPR/CAS9. EVs were isolated from the cell culture media by size exclusion column chromatography followed by detailed physical and chemical characterization. Physical characterization of EVs were accessed by tunable resistive pulse sensing and dynamic light scattering; revealed similar average sizes and zeta potentials (at pH7.4) for EVs from mIMCD (123.5 ± 5.7 nm and -16.3 ± 2.1mV), T1G cells (131.5 ± 8.3 nm and -19.8 ± 2.7mV) and T2J cells (127.3 ± 4.9 nm and -20.2 ± 2.1 mV). EVs derived from parental mIMCD cells and both mutated cell lines were heterogenous (>90% of EVs < 150 nm) in nature. Immunoblotting detected cilial Hedgehog signaling protein Arl13b; intercellular proteins TSG101 and Alix; and transmembrane proteins CD63, CD9, and CD81. Compared to Tsc2 deletion, Tsc1 deletion reduced the EVs production and release rate. Tsc1-EVs altered mTORC1, autophagy and β-catenin pathways differently than Tsc2-EVs. Quantitative PCR analysis revealed the downregulation of miR-212a-3p and miR-99a-5p in Tsc2-EVs as compared to Tsc1-EVs¬. Thus, EVs derived miR-212-3p/mTORC1 and mIR-99a-5p/mTORC1 axis could be a novel therapeutic target or biomarker for TSC disease.